2022
DOI: 10.1017/s002428292200007x
|View full text |Cite
|
Sign up to set email alerts
|

The globally threatened epiphytic cyanolichenErioderma pedicellatumdepends on a rare combination of habitat factors

Abstract: Lichen extinction occurs at rapid rates as a result of human activity, although species could potentially be rescued by conservation management based on ecophysiological knowledge. The boreal old forest cyanolichen Erioderma pedicellatum currently occurs in few sites worldwide. To protect it from extinction, it is essential to learn more about it. The last remaining good European site is a canyon with a waterfall, in a low-rainfall region of Norway. Here, a spatially restricted population of 1500–2000 thalli d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
(158 reference statements)
2
2
0
Order By: Relevance
“…Both lichens showed a positive logistic relationship with the number of rainy days; this confirms the theory that frequent inputs of liquid water (as rain or fog) are especially important for cyanolichens (Gauslaa 2014). Other recent work confirmed this experimentally, demonstrating that significant inputs of liquid water (≥1.7 mm, Gauslaa and Arsenault 2020), or fine water droplets such as those generated in proximity to waterfalls (Nilsson et al 2022), are required for E. pedicellatum to maintain full thallus hydration. Erioderma mollisimum showed a stronger association with high mean annual rainfall than E. pedicellatum, but moderate mean annual snowfall was exclusively associated with Erioderma pedicellatum.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Both lichens showed a positive logistic relationship with the number of rainy days; this confirms the theory that frequent inputs of liquid water (as rain or fog) are especially important for cyanolichens (Gauslaa 2014). Other recent work confirmed this experimentally, demonstrating that significant inputs of liquid water (≥1.7 mm, Gauslaa and Arsenault 2020), or fine water droplets such as those generated in proximity to waterfalls (Nilsson et al 2022), are required for E. pedicellatum to maintain full thallus hydration. Erioderma mollisimum showed a stronger association with high mean annual rainfall than E. pedicellatum, but moderate mean annual snowfall was exclusively associated with Erioderma pedicellatum.…”
Section: Discussionsupporting
confidence: 81%
“…Acer rubrum and Abies balsamea are both adapted to growing in acidic environments (i.e., peatlands) but are known for having less acidic bark than most co-occurring tree species (COSEWIC 2002); this buffering capacity of the bark would further delay any negative impacts on lichens beyond the point at which soil buffer capacities become exceeded (sensu Gilbert 1970). Recent measurements in forested wetlands of southwest Nova Scotia have confirmed that, at least with Acer rubrum bark, some buffering ability is likely still present, with pH values of 4-5 (Haughian, unpublished data), and research from other regions has shown a consistent association between Erioderma occupancy and high bark pH, even within a host tree (Nilsson et al 2022). On the other hand, the inputs of acid pollution that were incorporated into the acid threshold exceedance estimates originated from raster layers with a grid cell size of 35 × 35 km (Carou et al 2008), leading to a considerable homogenization over such a small area as Nova Scotia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the occurrence of many lichens, as indicated by our results, may be dependent on intermediate conditions where both humidity and light availability are at least moderate (Gauslaa et al 2006). Our data suggests that some species prefer an unusual combination of high humidity and high light availability (see also Nilsson et al 2022). Our results highlight that dense forests are inhospitable to many red-listed lichens (see also Gauslaa et al 2006;Gauslaa et al 2007;Klein et al 2020;Nirhamo et al 2021).…”
Section: Microclimatesupporting
confidence: 63%